2003
DOI: 10.1076/neur.9.6.482.29376
|View full text |Cite
|
Sign up to set email alerts
|

Metamemory Accuracy in Alzheimer’s Disease and Frontotemporal Lobe Dementia

Abstract: Metamemory is a multifaceted concept, which deals with an individual's knowledge and control of his or her own memory system. The ability to monitor memory performance accurately was examined in 16 patients with Alzheimer's disease (AD), 6 patients with frontotemporal lobe dementia (FTD) and 16 elderly subjects. Participants made global memory predictions in a single experimental task, both prior to and after studying 20 critical cue-target words. Prediction accuracy was evaluated with traditional score-differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 83 publications
0
40
2
Order By: Relevance
“…Only a subgroup of our patients could perform these tasks which required metamemory capacities that were shown to be impaired in fv-FTD (Souchay, Isingrini, Pillon & Gil, 2003). As previously shown with remember responses (Piolino et al, 2003), the fv-FTD patients who were able to carry out this kind of selfjudgment, experienced difficulty to subjectively "feel" that they were mentally reliving the source of their memories.…”
Section: Characteristics and Cognitive Mechanisms Of Am Deficits In Pmentioning
confidence: 75%
“…Only a subgroup of our patients could perform these tasks which required metamemory capacities that were shown to be impaired in fv-FTD (Souchay, Isingrini, Pillon & Gil, 2003). As previously shown with remember responses (Piolino et al, 2003), the fv-FTD patients who were able to carry out this kind of selfjudgment, experienced difficulty to subjectively "feel" that they were mentally reliving the source of their memories.…”
Section: Characteristics and Cognitive Mechanisms Of Am Deficits In Pmentioning
confidence: 75%
“…The same pattern of results has also been observed in patients with Alzheimer's disease (AD). AD patients were found to have a preserved semantic FOK (Bäckman & Lipinska, 1993;Lipinska & Bäckman, 1996) and an impaired episodic FOK (Souchay et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Note that for the calculation of Gamma, the measure is undefined when, two of the four possible outcome rates used to compute the Gamma scores (1, correct recognition of ''yes'' prediction; 2, incorrect recognition of ''yes'' prediction; 3, correct recognition of ''no'' prediction; 4, incorrect recognition of ''no'' prediction) are equal to 0. Thus, following Snodgrass and Corwin's (1988) recommendations (see Souchay, Isingrini, Pillon, & Gil, 2003), we corrected the raw data by adding 0.5 to each frequency and then dividing by N + 1 (where N is the number of judgments).…”
Section: Participantsmentioning
confidence: 99%
“…Several studies have shown that memory accounts for differences in metamemory across healthy elders and individuals with AD [101,102]. That is, group differences in metamemory disappear when memory is entered as a covariate in between group analyses.…”
Section: Dissociations In Metacognition In Ad and Implications For Momentioning
confidence: 99%
“…There are certainly reasons to expect such an association, including the substantial literature in both clinical and healthy populations implicating the role of the PFC in supporting executive functioning and aspects of self-awareness, and the conceptual similarities between executive functioning and memory monitoring. However, findings from empirical examinations of the relationship between objectively measured metamemory and executive function in AD and MCI do not support this idea [84,101,102]. A recent study designed to disentangle the cognitive correlates of metamemory in AD suggests that a specific cognitive domain may be less influential for metamemory than the extent to which a task relies on a critical set of brain regions [95].…”
Section: Dissociations In Metacognition In Ad and Implications For Momentioning
confidence: 99%